Social Responsibility According to Imam Al-Juwaini in his Book “Ghiyath al-Umam Fi Al-Thiath Al-Zulm”: A Fundamental Study - Hadi, أبرار أحمد عبدالله (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: This study aims to clarify the concept of social responsibility, clarify the roles of those involved in it, and then extract applied models that root them from the book of Al-Ghayathi by Imam Al-Juwayni and show their legal adaptation. This is in addition to proving that the Islamic heritage has dealt with the issue of social responsibility since ancient times, so it is not a new topic. Methods: A combination of descriptive, analytical, fundamental methodology was used , ‎which included induction and deduction approaches, because it fits the content of ‎the study and achieves its objectives. ‎ Results: The study reached a result that Al-Ghayathi’s book is a comprehensive reference of social responsibility, and the ruling of social responsibility is obligatory on whole nation, including rulers, religious jurists, scholars, rich and individuals, depending on their status, condition and ability. The fundamental forms of social responsibility in Al-Ghayathi have included both religious, political, economic and social dimensions. Islamic Law ‎adaptation has varied with the diversity of‏ ‏‎ forms‎. The rich must also obey the ruler by participating in social responsibilities in the event of crises and working to confront and solve them. It is permissible to impose taxes, as it is part of social responsibility. Conclusions: Paying attention to heritage books that root the current and emerging issues, which are many; also cooperation of the rich people with governments that have not imposed taxes to achieve social responsibility and address the negative effects of economic malpractice with Corona pandemic.